PENGARUH ALOKASI ANGGARAN PNPM MANDIRI PERKOTAAN TERHADAP KEMISKINAN DI KECAMATAN DELTA PAWAN KABUPATEN KETAPANG - B61110051, ismail (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT Economic growth Ketapang high, while unemployment and poverty is high. Economic development needs to be realized in plugging, at least reducing poverty, unemployment, and inequality. There have been many ways used by the government in terms of economic development, poverty alleviation programs that did little to pay, still not able to optimally solve the problem of poverty. The problems of poverty are still high that is the focus of this study, how good and right on target, whether the program PNPM Urban may be one solution of many existing government programs. To find in-depth research needs to be done to influence budgetary allocations PNPM - MP through Social, Economic, and Environmental toward poverty alleviation particularly in Ketapang District Pawan Delta. Results of tests performed using the normality test showed that both the dependent and independent variables to normal distribution, and based on the test results of this study do not contain multicollinearity multicollinearity between the independent variables and the dependent or independent variable stand alone / no link with the other independent variables, so that the test results good research. Hypothesis testing is based on the coefficient of determination (adjusted R2) between the dependent and independent variables have a pretty strong relationship. Based on the feasibility test model (F test) influence the budget allocation significantly affect poverty. Partial results of tests of significance, only the social sector variables (X1) which can reduce poverty, although the effect was not significant significance. While both economic sector variables (X2) and the environmental sector (X3) significant influence of significance but can actually increase poverty. Empirically can be explained due to the social sector budget allocations through right on target improving skills, improving education, and the provision of public health services. While budget allocations through the economy and the environment can be described empirically is not exactly on target and cultural factors/cultural wasteful, dishonest, not confident, and shut down that still dominates a cause of poverty and difficult alleviated particularly in Sub Delta Pawan Ketapang district. Keywords : Budget Allocation, Poverty Alleviation